Disneyizacje i disneyfikacje a produkcja kulturalna. Spojrzenie z perspektywy kulturowej historii nowoczesności - Płuciennik, Jarosław; Szul, Szymon (Zagadnienia Rodzajów Literackich, 2025)
This text attempts to provide a synthetic overview of the phenomena of Disneyization and Disneyfication in the context of the transformations occurring in the functioning of art worlds in the 20th and 21st centuries. The authors begin with Alan Bryman’s perspective to demonstrate the connections between consumer culture and cultural production, and then, through the lens of the cultural history of modernity, explain how the paradigmatic anti-experience of the early 20th century influenced the representation of reality and the development of film conventions at the Walt Disney studio. The researchers then attempt to frame Disney’s work within the model of art’s syncopated nature, understood not as a simple repetition of earlier forms, but as a rhythm of returns and shifts, in which each iteration carries an element of discontinuity. Syncopity is revealed here as a figure of tension — demonstrating that art, despite dispersion and fragmentation, maintains coherence precisely through constant transformation, not through the copying of fixed patterns. The article thus emphasises that contemporary artistic practices operate within a logic of dynamic difference rather than faithful repetition, opening the door to renewed reflection on persistence and change in visual culture. The following sections provide discussions about the articles comprised of the theme of this issue.